EFEKTIVITAS PELAKSANAAN PELAYANAN ADMINISTRASI KEPADA MASYARAKAT (STUDI KANTOR KELURAHAN BANDARA KECAMATAN SUNGAI PINANG KOTA SAMARINDA) - Hidayat, Rachmat (PREDIKSI, 2016)
The Effectiveness of Service of the Administrative services to the public (Study : at the offices of Kelurahan Bandara Kecamatan Sungai Pinang of Samarinda City). Under the guidance of dr. Marjoni Rachman, as mentor 1 and Mr Drs, H. Maskan, M. Si, as mentor II.Kelurahan Bandara Kecamatan Sungai Pinang as the area device carrying out the tasks of the ministry that includes 4 (four) field which consists of the Government, the field of development and areas of society. Public Services are the focus of the study discipline of public administration in Indonesia is still a problem that need to gain attention and a comprehensive solution where the various demands of public services as a sign of community daily dissatisfaction. Services is one of the cornerstones of the efforts of the customer satisfaction and is a necessity which it must be optimized either by individual or organization that provides services.the purpose of this study was to determine and analyze the work ability well as an inhibiting factor and supporting factors.The results showed that the quality of work discipline government officials sufficient is able to provide effective services to the community, so that every community who need services can be easily serviced. The process of services in general are in accordance with the expectations of society, But sometimes the service still lacking because of factors which are not unexpected. The sense of justice given by Kelurahan Bandara undifferentiated over status and economic level, but who apply first will be the first to be served.